2010
DOI: 10.1186/1471-2180-10-171
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptional profiling of Burkholderia pseudomallei under salt stress reveals differential effects on the Bsa type III secretion system

Abstract: BackgroundBurkholderia pseudomallei is the causative agent of melioidosis where the highest reported incidence world wide is in the Northeast of Thailand, where saline soil and water are prevalent. Moreover, recent reports indicate a potential pathogenic role for B. pseudomallei in cystic fibrosis lung disease, where an increased sodium chloride (NaCl) concentration in airway surface liquid has been proposed. These observations raise the possibility that high salinity may represent a favorable niche for B. pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 38 publications
7
47
0
Order By: Relevance
“…We also found that high salinity and high proportion of gravel were associated with the presence of B. pseudomallei (see Supplementary Information Figure 5). The association between presence of B. pseudomallei and high soil salinity is consistent with previous laboratory studies 22 . Although our model did not find an association between the presence of B. pseudomallei and soil pH reported by previous environmental studies 23 , this could be because soil pH is generally associated with other soil factors, particularly soil salinity 21 , reducing the capacity of our model to identify this as a geographic risk factor.…”
supporting
confidence: 92%
“…We also found that high salinity and high proportion of gravel were associated with the presence of B. pseudomallei (see Supplementary Information Figure 5). The association between presence of B. pseudomallei and high soil salinity is consistent with previous laboratory studies 22 . Although our model did not find an association between the presence of B. pseudomallei and soil pH reported by previous environmental studies 23 , this could be because soil pH is generally associated with other soil factors, particularly soil salinity 21 , reducing the capacity of our model to identify this as a geographic risk factor.…”
supporting
confidence: 92%
“…Genes differentially regulated in Bp isolated from infected mouse lungs were significantly enriched in 9 condition-dependent clusters (, hypergeometric test). One upregulated cluster C030, comprised T3SS3 genes, likely reflecting a strong functional requirement for T3SS3 activity during lung colonization [42]. Among the upregulated genes, we identified five that might function as potential effector proteins - BPSS1498 ( tssD-5 ), BPSL3319 ( fliC ), BPSS1525 ( bopE ), BPSS1529 ( bipD ) and BPSS1532 ( bipB ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results supported the results of a previous study that demonstrated that saline soil and water were the preferred growth conditions for B. pseudomallei in northeastern Thailand. 21 Moreover, the growth-promoting effect of iron on B. pseudomallei reinforced the significant association between B. pseudomallei-positive sites and the soil being reddish gray or reddish brown, indicating its iron content and the presence of animals. 19 Red to reddishyellow loamy sand containing iron and iron-impregnated nodules has been reported in the melioidosis-endemic area of Nam Phong catena in northeastern Thailand.…”
Section: Discussionmentioning
confidence: 84%
“…17 The association of the presence of B. pseudomallei with that of iron and salt in water and soil has been demonstrated in endemic areas. 16,[18][19][20][21][22] These results may facilitate understanding of the ability of B. pseudomallei to adapt to soil in northeastern Thailand that has different environmental features, including high salinity and the presence of iron. The resilience exhibited by B. pseudomallei in endemic areas has resulted in a high risk of pathogen exposure.…”
Section: Introductionmentioning
confidence: 99%